OS EFEITOS TERRITORIAIS DA EXPANSÃO DO CAPITAL E A TRANSFORMAÇÃO DO ESPAÇO URBANO NA CIDADE DE TRÊS LAGOAS-MS ENTRE OS ANOS DE 2000 A 2020 - João Luiz Da Silva (2021)
From the 2000s, the municipality of Três Lagoas MS began to experience a rapid growth of its industrial park. This was due to attempts by the Brazilian State to decentralize the industrial complex, originally concentrated mainly in the Southeast, in particular São Paulo. The objective of this dissertation is to try to understand the territorial effects of this capital expansion and the transformation of the urban space in the city of Três Lagoas-MS, with a period between the years 2000 to 2020. The qualitative analysis of the empirical data as much as the bibliographic research sought to identify the factors that contributed to the beginning of this industrialization process, and through the empirical data collected from public agencies and observations made by the author in fieldwork, we identified that the demographic growth caused by the coming of a large number of workers for the city generated a significant increase in real estate speculation, which in turn caused the expansion of the urban fabric of the city of Três Lagoas as well as the emergence of segregated spaces as the main ones. We also noticed that this industrialization process in Três Lagoas was propitiated through the construction, by the State, of an infrastructure geared to meet the needs of expansion of the big capital with the construction of highways connecting the coast to the interior of the country, the creation of a telecommunications network that would allow the management of new branches from the city of São Paulo, technological advances in the areas of commodity agriculture, expanding the agricultural frontier to the Midwest region, and also in the creation of tax incentives for stimulate the movement of industry to more distant regions. This whole set of State actions added to the natural resources available in the Três Lagoas region, such as: lands of pastures already deforested and flat topography that facilitates eucalyptus monoculture, transformed the municipality into an attractive area for the expansion of big capital. Thus, from the year 2000, the city began to experience a great growth in its industrial park. This industrialization process gained momentum with the arrival of two large industrial pulp and paper plants in 2006, International Paper, now Suzano, and Eldorado Brasil Papel e Celulose, considered the largest papermakers in the country. Together with them, other companies have also installed themselves in the place, which have caused a series of social and physical impacts and influenced the transformation of their urban space. Within the objective of this work to study these effects of the capital expansion in Três Lagoas-MS, we are aware of the impossibility of presenting in this text all or even a large number of these effects, so we focus primarily on the agents that most influenced the transformation of the urban space of the city.